2018
DOI: 10.1037/xlm0000554
|View full text |Cite
|
Sign up to set email alerts
|

Increased cognitive load enables unlearning in procedural category learning.

Abstract: Interventions for drug abuse and other maladaptive habitual behaviors may yield temporary success, but are often fragile and relapse is common. This implies that current interventions do not erase or substantially modify the representations that support the underlying addictive behavior — that is, they do not cause true unlearning. One example of an intervention that fails to induce true unlearning comes from Crossley, Ashby, and Maddox (2013, Journal of Experimental Psychology: General), who reported that a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
(47 reference statements)
0
4
0
Order By: Relevance
“…Attending and resident physician groups reported an average overall CL of 5 using the nine-point Paas Scale, which falls within the range for optimal learning and performance (score of 3-6 out of 9) as reported by Fraser et al 26 Therefore, according to psychometric measures of CL reported in this acute care setting, current patient case load did not appear to overwhelm limits of WM to cause significant cognitive overload. This is a significant finding as cognitive overload has been associated with unlearning, 27 mental burnout, and patient errors. 28 It is important to consider that though both the attending and the resident groups had similar measures of CL, attending physicians carried a significantly higher patient load at any given time, suggesting that attending EM physicians were able to do more with the same investment of mental effort as residents.…”
Section: Discussionmentioning
confidence: 99%
“…Attending and resident physician groups reported an average overall CL of 5 using the nine-point Paas Scale, which falls within the range for optimal learning and performance (score of 3-6 out of 9) as reported by Fraser et al 26 Therefore, according to psychometric measures of CL reported in this acute care setting, current patient case load did not appear to overwhelm limits of WM to cause significant cognitive overload. This is a significant finding as cognitive overload has been associated with unlearning, 27 mental burnout, and patient errors. 28 It is important to consider that though both the attending and the resident groups had similar measures of CL, attending physicians carried a significantly higher patient load at any given time, suggesting that attending EM physicians were able to do more with the same investment of mental effort as residents.…”
Section: Discussionmentioning
confidence: 99%
“…Ryu and Torres (2018) found that the change of cognitive load could significantly alter task performance in terms of accuracy and time management. Crossley et al (2018) and Bi et al (2019) further verified the effects of cognitive load on individuals' task performance. However, these prior studies were largely limited to 2-dimensional image-based static site scenarios, which could not fully capture the more complicated, interactive, and dynamic real site environment that individuals face.…”
Section: Introductionmentioning
confidence: 91%
“…Unlearning has been researched within the domain of psychology with regard to addiction (Crossley et al , 2018) and social bias (Aczel et al , 2015) as well as within the realm of organizational unlearning (Nguyen, 2017). However, psychologists have also argued that unlearning cannot occur (Howells and Scholderer, 2016).…”
Section: Unlearning In Psychologymentioning
confidence: 99%